2016
DOI: 10.5021/ad.2016.28.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Quantification of Glycosaminoglycans from Human Hair Shaft

Abstract: BackgroundThere is evidence that glycosaminoglycans (GAGs) are present in the hair shaft within the follicle but there are no studies regarding GAGs isolation and measurement in the human hair shaft over the scalp surface, it means, in the free hair shaft.ObjectiveThe purpose of our research was to isolate and measure the total GAGs from human free hair shaft.MethodsSeventy-five healthy individuals participated in the study, 58 adults, men and women over the age of 50 and 17 children (aged 4~9). GAGs in hair s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…We contextually detected a significant difference in predicted pathways associated with glycosaminoglycan (GAG) degradation in AA samples. From a clinical perspective, alterations of GAG degradation induce mucopolysaccharidoses and abnormalities in hair morphology (Malinowska et al, 2008), and studies in patients with hair loss revealed a reduction in GAGs in the connective tissue around the follicle, suggesting their importance for structure and density maintenance (Maniatopoulou et al, 2016). According to Cole and collaborators (Cole et al, 2011), bacteria can use GAGs, especially hyaluronan, to mask themselves, avoiding recognition by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…We contextually detected a significant difference in predicted pathways associated with glycosaminoglycan (GAG) degradation in AA samples. From a clinical perspective, alterations of GAG degradation induce mucopolysaccharidoses and abnormalities in hair morphology (Malinowska et al, 2008), and studies in patients with hair loss revealed a reduction in GAGs in the connective tissue around the follicle, suggesting their importance for structure and density maintenance (Maniatopoulou et al, 2016). According to Cole and collaborators (Cole et al, 2011), bacteria can use GAGs, especially hyaluronan, to mask themselves, avoiding recognition by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have revealed that hair follicules express a distinctive composition of proteoglycans that contrasts with their surrounding dermal environment [16]. Interestingly, the distribution of these specialised proteoglycans undergoes dramatic alterations throughout a hair growth cycle [15,17]. is dynamic expression pattern and its plausible functional relevance are described in this section.…”
Section: The Presence Of Proteoglycans Inside the Hair Folliclementioning
confidence: 87%
“…Indeed, the alterations of GAG degradation have been reported as responsible of abnormalities in hair morphology [ 39 ] and of the alteration of the morphology of the connective tissue surrounding the HF [ 64 ]. Bacteria themselves can use GAGs, as a mask to avoid the recognition by the immune system collaborators [ 65 ].…”
Section: Discussionmentioning
confidence: 99%